Implementation of ESP32-Based Web Host For Control and Monitoring of Robotic Arm - Sutarsi Suhaeb; Ahmad Risal (Journal of Embedded Systems, Security and Intelligent Systems, 2024)
In the modern technological era, the Internet of Things (IoT) plays a significant role in developing robotic control systems, including robotic arms. This study explores the implementation of an ESP32-based webhost to control and monitor robotic arm operations in real time via a web interface connected to a Wi-Fi network. The system is designed to provide ease of access, reliable performance, and low latency, making it suitable for education, technical training, and other applications. Testing revealed that the system delivers fast response times, high stability under moderate loads, and an intuitive interface for users with varying skill levels. These findings present opportunities for further development, including integration with cloud-based technologies and data security enhancements